2020
DOI: 10.3389/fpsyt.2020.00776
|View full text |Cite|
|
Sign up to set email alerts
|

Combined Effects of Parenting in Childhood and Resilience on Work Stress in Nonclinical Adult Workers From the Community

Abstract: Background: Stress responses induced by job stressors are modified by individual factors. Perceived parental bonding and resilience would play important roles as such individual factors. In this study, we analyzed the mediating roles of resilience on parenting, job stressors, and stress responses among adult workers from the community. Methods: A total of 528 workers participated in this study after providing written consent, and completed questionnaires on demographic data, as well as Parental Bonding Instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Regarding workers’ mental health, research has shown that childhood parental bonding, neuroticism, and resilience affect work-related stress in adult workers [ 51 , 52 ]. Furthermore, sleep disturbance and work-related stress affect presenteeism [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding workers’ mental health, research has shown that childhood parental bonding, neuroticism, and resilience affect work-related stress in adult workers [ 51 , 52 ]. Furthermore, sleep disturbance and work-related stress affect presenteeism [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…19,22,23 Job stressors, which are reportedly affected by childhood parenting, resilience, and neuroticism, induce psychological and physical responses in workers. 24,25 Job stressors are a mediator among childhood parenting, resilience, neuroticism, and psychological and physical responses. 24,25 Taken together with the previous findings mentioned above regarding the associations among adverse stresses in childhood, including victimization, neuroticism, depression, and presenteeism, 1,2,6,21,22,[24][25][26] it can be assumed that childhood victimization influences neuroticism, job stressors, and presenteeism.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Job stressors are a mediator among childhood parenting, resilience, neuroticism, and psychological and physical responses. 24,25 Taken together with the previous findings mentioned above regarding the associations among adverse stresses in childhood, including victimization, neuroticism, depression, and presenteeism, 1,2,6,21,22,[24][25][26] it can be assumed that childhood victimization influences neuroticism, job stressors, and presenteeism. However, these associations of childhood victimization with neuroticism, job stressors, and presenteeism have not yet been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the impact of subjective cognitive dysfunction on workers, subjective cognitive dysfunction may affect presenteeism directly and mediate the influence of depressive symptoms on presenteeism in workers 9 ) . A recent study suggests that parental bonding and resilience affect job-related stress in workers 35 ) . Furthermore, job-related stress and sleep disturbance have been reported to affect presenteeism in office workers 36 ) .…”
Section: Discussionmentioning
confidence: 99%